Glucose transport across the blood-brain barrier - Leybaert, Luc (Henry Stewart Talks, 2008)
Functions of the neurovascular unit, Brain energy substrates, Pathways across the blood-brain barrier, Glucose utilization and transport, Glucose uniporters, Kinetic transport parameters, Glucose transport in baseline and during activation, Neurovascular coupling, Neurometabolic coupling, Neurobarrier coupling, Dynamic changes of glucose concentration, GLUT-1 stimulation in vitro and in vivo, Roadmaps for glucose from blood to neurons
Archived at 2018/10/28